Theiler's virus genome is closely related to that of encephalomyocarditis virus, the prototype cardiovirus. - Ozden, S (1986)
Theiler's virus causes a persistent demyelinating infection of the mouse central nervous system. Our study of the molecular mechanism of persistence led us to sequence 1925 nucleotides located at the 3' end of the viral genome. We observed extensive homologies between this region and the corresponding region of encephalomyocarditis virus, the prototype cardiovirus, and only some homologies with the 3' ends of foot-and-mouth disease virus, rhinovirus, and poliovirus genomes.